2016
DOI: 10.1111/ajt.13613
|View full text |Cite
|
Sign up to set email alerts
|

CD57+ CD4 T Cells Underlie Belatacept-Resistant Allograft Rejection

Abstract: Belatacept is a B7-specific fusion protein used to prevent allograft rejection by blocking T cell costimulation. Generally efficacious, it fails to prevent acute rejection in a sizable minority of patients. In experimental models, memory T cells mediate costimulation blockade-resistant rejection (CoBRR), but this remains undefined in humans. To explore relationships between individuals’ immune cell phenotypes and CoBRR, we studied patients receiving belatacept or conventional calcineurin inhibitor-based immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 38 publications
9
135
2
Order By: Relevance
“…Current research efforts by our group and others seek to define potential immunologic parameters that might identify those patients at risk of rejection when treated with belatacept. (21, 22) Accurate identification of those patients who are at low risk of rejection may permit us to stratify those to avoid adjunct tacrolimus treatment as well as determine the optimal timing of the transition off of tacrolimus therapy for others.…”
Section: Discussionmentioning
confidence: 99%
“…Current research efforts by our group and others seek to define potential immunologic parameters that might identify those patients at risk of rejection when treated with belatacept. (21, 22) Accurate identification of those patients who are at low risk of rejection may permit us to stratify those to avoid adjunct tacrolimus treatment as well as determine the optimal timing of the transition off of tacrolimus therapy for others.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, de Graav et al (14) reported the downregulation of surface CD28 on both CD4 + and CD8 + T cells as a potential escape mechanism from belatacept-mediated immune suppression. More recently, Espinosa et al (3) reported in a small study of 14 transplant recipients that the pretransplant frequency of a highly functional CD4 …”
Section: Ccr7mentioning
confidence: 99%
“…The relatively high incidence of early aggressive T cell-mediated acute rejection is a significant impediment to the widespread use of belatacept in clinical transplantation, despite recent reports of improved long-term outcomes (1)(2)(3). High frequencies of alloreactive memory T cells have emerged as the major hypothesis to explain this emergence of belatacept-resistant cellular rejection.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the loss of CD28 on CD4 T cells has been implicated in promoting immunosuppression resistance and allograft rejection (6970) due to the cytotoxic capacity of these cells. Very recently it was reported that increases in circulating CD4 + CD28 − CD57 + T cells prior to transplantation is associated with belatacept resistant rejection (BRR) post-transplantation (7172). Furthermore, cytomegalovirus-related, cytotoxic CD4 + CD28 − T cells potentiate kidney allograft dysfunction by glomerular endothelial injury in an NKG2D-dependent manner.…”
Section: Clinical Relevance Of Cd4+cd28− T Cellsmentioning
confidence: 99%